Influência de aspectos técnicos e anatômicos nos índices de fertilidade baseado no desempenho da inseminação artificial - Taqueda, Gustavo Santos; Azevedo, Hymerson Costa; Santos, E. M.; Matos, José Eduardo; Bittencourt, Rodrigo Freitas; Bicudo, Sony Dimas [UNESP] (My University, 2011)
The aim of this work was to examine both the influence of anatomical and technical aspects on fertility rate of sheep based on the performance of transcervical artificial insemination (TCAI). Transcervical artificial insemination was performed with traction of the cervix in 122 ewes using frozen semen from 11 rams, both Santa Ines breed. The data collected were: type of external cervical opening (CO) (P - papilla; FL - flap; DB - duckbill, S - spiral; RO - rosette), duration of cervical manipulation (2-3, 4-5 and 6-7 minutes), degree of difficulty in cervical transposition (low, moderate, high) and presumed semen deposition site (SC - superficial cervical; DC - deep cervical; IU - intrauterine). The influence of these variables on pregnancy rate was evaluated. Cervical opening type and duration of cervical manipulation had no influence (p>0.05) on fertility. The degree of difficulty in cervical manipulation influenced (p<0.05) pregnancy rate, since insemination classified as low grade had 52% of pregnancy, while those classified as high recorded only 20%. The presumed site of semen deposition influenced significantly (p<0.05) fertility. Pregnancy rates of deposition at each site were: UI – 45.8%, DC – 25.7%; SC – 15.4%. As expected, deeper depositions resulted in higher fertility. In conclusion, the performance of TCAI did not depend on the anatomical classification of external cervical opening of ewe and the duration of cervical manipulation within the range tested (2-7 minutes). The TCAI may have higher fertility rates if difficulties in the application were reduced and the semen deposition was deeper.

Este trabalho teve como objetivo analisar a influência de aspectos técnicos e anatômicos no desempenho da inseminação artificial transcervical (IATC), sobre a fertilidade em ovinos. Foram realizadas inseminações artificiais transcervicais com tração da cérvix em 122 ovelhas sendo utilizado sêmen congelado de 11 carneiros, todos os animais da raça Santa Inês. Durante a inseminação foram coletados dados como o tipo de orifício superficial da cérvix (OS: P - papila; FL – flap; BP - bico de pato; ES – espiral; FD - flor desabrochada), duração da manipulação cervical (2 a 3, 4 a 5 e 6 a 7 minutos), grau de dificuldade na transposição cervical (baixo, moderado e alto) e local presumido de deposição do sêmen (CS – cervical superficial; CP– cervical profundo; IU – intrauterino). Avaliou-se a influência destas variáveis sobre a fertilidade refletida pela taxa de prenhez. Os tipos de OS e a duração da manipulação cervical não apresentaram influência (p>0,05) sobre a fertilidade. O grau de dificuldade na manipulação cervical influenciou (p<0,05) a taxa de prenhez: fêmeas que apresentaram baixo grau obtiveram 52%, enquanto aquelas com alto grau obtiveram apenas 20% de prenhez. Da mesma forma, o local presumido de deposição do sêmen influenciou significativamente (p<0,05) a taxa de fertilidade. As taxas de prenhez em cada local de deposição foram as seguintes: IU - 45,83%; CP – 25,7%; CS - 15,4%. Como era esperado, deposições mais profundas acarretaram em maior fertilidade. Conclui-se que o desempenho da IATC independe da classificação anatômica do orifício superficial cervical da ovelha e da duração da manipulação cervical dentro do intervalo testado (2 a 7 minutos). A IATC pode apresentar maiores taxas de fertilidade desde que se diminua a dificuldade em sua aplicação e se promova a deposição do sêmen mais profundamente.
Influence of anatomical and technical aspects on fertility rate based on sheep transcervical artificial insemination performance
Keywords: Cervix; Superficial opening; Cervical traction; Sheep